Protozoocidal activity of Stemona collinsiae against Giardia duodenalis - Khuanchai Koompapong; Supaluk Popruk; Onrapak Reamtong; Tipparat Thiangtrongjit; Sumate Ampawong; Aurapa Sakulpanich; Ruenruetai Udonsom; Kanthinich Thima; Preeyaporn M. Sreepian; Kittiyod Poovorawan; Hirotake Mori; Christen Rune Stensvold; et al. (Heliyon)
Giardia duodenalis is a major pathogen of the gastrointestinal tract, and infections impact both human health and the economy. The ongoing issues with drug resistance and the side effects of current anti-Giardia treatments highlight the urgent need for new therapeutic options. This study focused on investigating the in vitro efficacy of crude extracts of Stemona collinsiae from Thailand against G. duodenalis. S. collinsiae was initially extracted with hexane, followed sequentially by dichloromethane, ethanol, and water. The extracts were tested for growth inhibition against G. duodenalis. Dichloromethane and hexane extracts were highly active against the parasite after 48 h of exposure, with half-maximal inhibitory concentration (IC50) values of 60.77 μg/mL and 66.66 μg/mL, respectively. Both extracts reduced G. duodenalis trophozoite motility and adherence, altered trophozoite architecture, and induced apoptosis. Our findings demonstrate the anti-Giardia activity of S. collinsiae root extracts, especially those of dichloromethane and hexane. Our results will support the potential development of new and effective medications for the treatment of giardiasis.